Symptom clusters in cancer patients: An Italian survey to validate and describe unwarranted clinical variation, inequality in access to healthcare, knowledge, and risk of malpractice: Italian national survey on symptom clusters - Beloni, Silvia; Arrigoni, Cristina; Dellafiore, Federica; Diamanti, Orejeta; Piredda, Alessio; Caruso, Rosario (Acta Biomedica Atenei Parmensis, 2021)
Background and aims: The perceptions of professionals involved in cancer care regarding the importance of their symptoms-specific knowledge, unwarranted clinical variation (UCV), and inequalities in access to healthcare are still underdescribed. This study aims to confirm the construct validity of a previously initially developed questionnaire and describe nurses' perceptions about the relevance of their knowledge referred to cancer symptoms management, the UCV, the inequalities in access to healthcare, and malpractice risk.Method: A cross-sectional pan-national study was conducted using a convenience sample, collecting data through a previously initially validated questionnaire. Construct validity was corroborated through confirmatory factor analysis, and descriptive statistics were employed for summarizing the questionnaire's scores. The scores between the nurses working in accredited cancer centers and nurses employed in general hospitals were inferentially compared.Results: The sample comprised 810 nurses, 480 were nurses working in accredited cancer centers, and 330 were nurses working in general hospitals. The questionnaire showed adequate construct validity and reliability. Nurses perceived the cluster of psychosocial symptoms with a greater risk of UCV and inequalities in access to cancer services than the cluster of physical symptoms.Discussion and conclusions: A paradigm shift aimed at integrating psychosocial cancer symptoms in the care paths emerged as pivotal for improving Italy's cancer care.